1991
DOI: 10.1111/j.1600-0536.1991.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse skin reactions to nicotine in a transdermal therapeutic system

Abstract: Nicotine in a transdermal therapeutic system (TTS) has been introduced recently to help people to stop smoking. 14 volunteers (10 male, 4 female) with a history of former adverse skin reactions to this device were investigated. Skin tests for contact urticaria and patch tests for contact allergy were done with the individual components of the TTS. Contact sensitization to nicotine was identified in 5 and to the TTS itself in 1 individual. Irritant reactions due to occlusion were present in 9 subjects. The opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…It must be emphasized that this patient was a heavy smoker. In a study of 15 patients [9] contact sensitization to nicotine was identified in 5 and to transdermal system itself in 1 individual. Irritant reactions due to occlusion were present in 9 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized that this patient was a heavy smoker. In a study of 15 patients [9] contact sensitization to nicotine was identified in 5 and to transdermal system itself in 1 individual. Irritant reactions due to occlusion were present in 9 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study recruited 20 healthy men with normal skin. Previous research has investigated skin reaction in 14 volunteers with a history of adverse skin reactions to a nicotine patch and found that atopy and contact sensitization to standard patch test allergens were identified in 6 participants (12). Therefore, it is necessary to gather data in a large, diverse population that includes persons with sensitive skin.…”
Section: Discussionmentioning
confidence: 99%
“…Although nicotine is not a highly reactive chemical substance (12), the majority of allergic reactions reported with nicotine patches is attributed to nicotine (11). Since the minor occurrences of allergic reaction to nicotine are inevitable, varying the site of drug administration is recommended to minimize skin reactions (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations